Overview of Nutritional Status and Menstrual Cycle Disorders in Adolescent Girls in Tumpaan Village - Ribka Fanya Yuri Tiwow; Nancy S. Bawiling; Deviana Pratiwi Munthe (Universitas Muhammadiyah Palu, 2026)
This study aims to determine the nutritional status and menstrual cycle disorders in adolescent girls in Tumpaan Village. This study used a quantitative approach with a descriptive cross-sectional design. The study sample consisted of 76 respondents selected using a purposive sampling technique. The data collected included respondent characteristics, nutritional status, and menstrual cycle patterns, then analyzed univariately to obtain the frequency distribution of each variable studied. The results showed that most adolescent girls had normal nutritional status (44 respondents (57.89%), followed by overweight (16 respondents (21.05%), obesity (10 respondents (13.16%), and malnutrition (6 respondents (7.89%). In addition, it was found that 41 respondents (53.95%) experienced menstrual cycle disorders, while 35 respondents (46.05%) had normal menstrual cycles. In general, the results of this study provide an overview that the nutritional condition of adolescent girls in Tumpaan Village tends to be in the good category, although there are still cases of malnutrition, overweight, and obesity. The presence of adolescents experiencing menstrual cycle disorders also indicates the need for attention to diet, physical activity, and reproductive health education to support the physical and hormonal well-being of adolescent girls.